Spatial pattern analysis of thicket expansion in a semi-arid savanna - Putzier, Rachel Rayne (Rhodes University, Faculty of Science, Botany Department)
Woody thickening has negative economic and ecological impacts in savannas globally. While the increase of savanna trees as a form of bush encroachment has been well studied, less is known about the increase of thicket species in savannas, which is an important phenomenon resulting in the formation of closed-canopy clumps which may exclude the grass layer over time. The early stage of thicket expansion is often initiated by a nucleating savanna species which facilitates the establishment of woody thicket pioneer species, and as the thicket clump formation expands, bush clumps increase in dominance, thereby increasing the frequency of competitive interactions and leading to a possible switch from facilitative to competitive interactions. Spatial point pattern analysis provides a useful tool to elucidate these underlying patterns and ecological processes. I used high resolution LiDAR data combined with spatial point pattern analysis to understand tree-tree interactions in a semi-arid savanna in the Eastern Cape Province of South Africa. I conducted a cluster analysis based on vegetation structural variables to distinguish different stages of woody plant encroachment from open savanna to closed canopy thicket. Using the canopy height model, I quantified the change in the grass height from open savanna to closed canopy thicket clumps as an indicator of a possible biome shift. Additionally, I used spatial point pattern analyses to investigate the effect of thicket clump formation on the composition of savanna and thicket species, the overall patterns of trees, and the associations of small thicket species with large Vachellia karroo trees, which serve as clump initiators. Finally, I examined the mortality of savanna trees across increasing stages of thicket expansion using second order spatial statistics, namely the Mark- and Pair-Correlation Functions. Results confirmed that three vegetation states, influenced by elevation, are present at the study site, representing open canopy savanna (early-stage thicket encroachment), encroached savanna with low thicket dominance (intermediate-stage thicket encroachment), and highly encroached with dominant thicket clumps (late-stage thicket encroachment). These stages showed increasing tree height, canopy cover and canopy height density, as well as decreased (but not completely absent grass layer) as thicket encroachment progresses. Spatial point pattern analysis showed, as predicted, that there was an overall aggregation of trees at small-scales within early thicket clump formation, from which I inferred that facilitative relationships may exist between trees. Contrary to my predictions, at later stages of thicket clump formation I found dominant independent patterns between savanna adults and juvenile thicket species, which may result from a combination of facilitative and competitive effects. Lastly, as expected, I found that the density of V. karroo mortality increased as thicket encroachment increased, with an overall random spatial pattern of dead V. karroo across encroachment stages. As predicted, tree mortality was randomly distributed in space in the open savanna state, and as thicket clump formation increases, tree competitive mortality became more evident, as well as decreased tree performance. Overall, the study highlights the interplay between facilitation and competition in semiarid savanna where thicket clumps are expanding. Intervention strategies are suggested to target areas of intermediate thicket clump formation, as these areas provide an opportunity to remove V. karroo before the nucleation process has enabled the establishment and increase of thicket species and to ensure the grass layer is kept productive. I conclude that the use of remote sensing and LiDAR technology holds a wide range of possibilities for monitoring and managing woody encroachment in savanna systems, however these methods need to be further refined for effective use within African savanna and thicket context, which displays high spatial aggregation making typical segmentation methods difficult.
Keywords: Arid regions -- South Africa -- Eastern Cape; Spatial analysis (Statistics); Thicket; Lidar; Cluster analysis; Trees Mortality; Scrub encroachment